2021
DOI: 10.3390/biom11121803
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits and Pharmacological Properties of Carvone

Abstract: Carvone is a monoterpene ketone contained in the essential oils of several aromatic and medicinal plants of the Lamiaceae and Asteraceae families. From aromatic plants, this monoterpene is secreted at different concentrations depending on the species, the parts used, and the extraction methods. Currently, pharmacological investigations showed that carvone exhibits multiple pharmacological properties such as antibacterial, antifungal, antiparasitic, antineuraminidase, antioxidant, anti-inflammatory, and antican… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 105 publications
(197 reference statements)
0
36
0
1
Order By: Relevance
“…The CAS number of this article is 5-75-8006. Based on a pre-clinical experimental study, this substance has a statistically significant sedative effect against increased excitement [13,31,32]. Carvacrol is a monoterpene phenolic compound with a structure of 5-isopropyl -2-methyl phenol and a chemical formula of C10H14O [33].…”
Section: Discussionmentioning
confidence: 99%
“…The CAS number of this article is 5-75-8006. Based on a pre-clinical experimental study, this substance has a statistically significant sedative effect against increased excitement [13,31,32]. Carvacrol is a monoterpene phenolic compound with a structure of 5-isopropyl -2-methyl phenol and a chemical formula of C10H14O [33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, researchers have been searching for alternatives to conventional antibiotics. Within this context, natural substances, particularly those extracted from medicinal plants, constitute a source of drugs against various pathologies, including diabetes, cancer, inflammation, and pathologies linked to stress and microbial infections [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The antibacterial activity of these natural products is linked to different mechanisms of action, such as the increase in membrane permeability, the decrease in membrane integrity, and the disruption of efflux pumps [ 10 , 13 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, only around 5%–15% of the roughly 250,000 higher plants have ever been studied for pharmacological activities [ 2 ]. Numerous studies conducted over the last few decades have shown that research on therapeutic plants is critical and bioactive phytochemicals or bionutrients are abundant in medicinal plants; these phytochemicals have a critical role in avoiding chronic illnesses such as cancer [ 3 5 ], diabetes [ 6 9 ], and coronary heart disease [ 10 12 ]. Dietary fiber, detoxifying agents, antioxidants, anticancer, neuropharmacological agents, and immune-stimulating agents are the key groups of phytochemicals having disease-preventive properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%